Effectiveness of Implementation of Guidance and Counseling to Lower Levels Bullying in Elementary School - Kadek Ari Wisudayanti; Putu Yulia Angga Dewi (STAHN Mpu Kuturan Singaraja, 2023)
Bullying is the aggressive and negative behavior of a person or group of people repeatedly who abuses an imbalance of power with the aim of hurting the target (victim) mentally or physically. The problem of bullying at school is the responsibility of all parties in the school and parents of students. Bullying in schools is a major problem that must be addressed because schools should protect their students from acts of violence in any form, and become a vehicle for the formation of reason, morals and character needed to build a healthy, cultured and high-tech Indonesian society.